High‐Resolution Manometry Improves the Diagnosis of Esophageal Motility Disorders in Patients With Dysphagia: A Randomized Multicenter Study. (March 2016) - Roman, Sabine; Huot, Laure; Zerbib, Frank; des Varannes, Stanislas Bruley; Gourcerol, Guillaume; Coffin, Benoit; Ropert, Alain; Roux, Adeline; Mion, François
Abstract : Objectives: High‐resolution manometry (HRM) might be superior to conventional manometry (CM) to diagnose esophageal motility disorders. We aimed to compare the diagnosis performed with HRM and CM and confirmed at 6 months in a multicenter randomized trial. Methods: Patients with unexplained dysphagia were randomized to undergo either CM or HRM. Motility disorders were diagnosed using the Castell and Spechler classification for CM and the Chicago classification for HRM. Diagnosis confirmation was based on clinical outcome and response to treatment after 6‐month follow‐up. The initial diagnosis and percentage of confirmed diagnoses were compared between the two arms (CM and HRM). Results: In total, 247 patients were randomized and 245 analyzed: 122 in the CM arm and 123 in the HRM arm. A manometric diagnosis was more frequently initially achieved with HRM than with CM (97% vs. 84%; P <0.01). Achalasia was more frequent in the HRM arm (26% vs. 12% in the CM arm; P <0.01) while normal examinations were more frequent in the CM arm (52% vs. 28% in the HRM arm; P <0.05). After follow‐up, the initial diagnosis was confirmed in 89% of patients in the HRM arm vs. 81% in the CM arm ( P =0.07). Finally, overall procedure tolerance was better with CM than with HRM ( P <0.01). Conclusions: This randomized trial demonstrated an improved diagnostic yield for achalasia with HRM compared with CM. Diagnoses tended to be more frequently confirmed in patients who underwent HRM, suggesting that esophageal motility disorders could be identified earlier with HRM than with CM (ClinicalTrial.gov, NCT01284894).